Back to Course

0% Complete
0/0 Steps

• ## Do you like this content?

Lesson 8, Topic 1
In Progress

# Simultaneous Linear Equations

Lesson Progress
0% Complete

### Algebraic Solution

This involves:

1. Substitution Method
2. Elimination Method

### Substitution Method

Example 1

Use the substitution method to solve the following pairs of simultaneous equations

(a) q + 2r = 8;          r – $$\frac{q}{2}$$ + 1 = 0

(b) y – $$\frac{x}{4}$$ = 3; Â  Â  Â  Â  3y + x = 23

Solution:

(a) $$\scriptsize r \; – \; \normalsize \frac {q}{2} \scriptsize + 1 = 0$$

Re-write as Â  $$\scriptsize r\; -\; \normalsize \frac {q}{2} \scriptsize = -1$$

Multiply both sides by 2

i.e.     2r â€“ q = -2         …………(1)

2r + q = 8          …………(2)

i.e.     q = 8 â€“ 2r         ………….(3)

Substitute for q in equation (1)

i.e.     2r â€“ (8 â€“ 2r) = -2 (Expand brackets)

i.e.     2r â€“ 8 + 4r = -2

i.e.     6r â€“ 8 = -2 (Collect like terms)

i.e.     6r = 6 (Divide both sides by 6)

i.e.     r = 1

Substitute for r in equation (3)

i.e.     q = 8 â€“ 2(1)

i.e.      q = 8 â€“ 2

i.e.      q = 6.

Check:

2r + q = 8

2(1) + 6 = 8

2 + 6 = 8

8 = 8

(b) Â  Â  $$\scriptsize y\; – \; \normalsize \frac {x}{4} \scriptsize = 3$$

Multiply both sides by 4

4y â€“ x = 12         ……….(i)

3y + x = 23 Â  Â  Â  Â  â€¦â€¦â€¦â€¦â€¦â€¦..(ii)

i.e.          x = 23 – 3y              â€¦â€¦â€¦â€¦â€¦.(iii)

Substitute for x in equation (i)

i.e.       4y – 23 – 3y = 12

i.e.       4y – 23 + 3y = 12

i.e.       7y = 35

i.e.        y = 5

Substitute for y in equation (iii)

i.e.      x = 23 â€“ 3(5)

x = 23 -15

x = 8

Check:

3y + x = 23

3(5) + 8 = 23

15 + 8 = 23

23 = 23

### Elimination Method:

Example 2

Use elimination method to solve the following pairs of simultaneous equations:

(a) p + r = $$\frac{1}{4}$$;Â  Â  Â  Â  Â  Â  Â  5p + 2r = 2

(b) 3p – 2r = 21; Â  Â  Â  4p + 5 r= 5

Solution:

(a) 5p + 2r = 2Â  Â  Â  Â  Â  â€¦â€¦â€¦â€¦.(i)

Divide both sides by 2

i.e.      $$\frac{5}{2} \scriptsize p + r = 1$$     â€¦â€¦â€¦â€¦.(ii)

p + r = $$\frac{1}{4}$$          â€¦â€¦â€¦â€¦..(iii)

Subtract equation (iii) from (iii) to eliminate

i.e. $$\left ( \frac{5}{2} \scriptsize p \; – \; p \right) + \scriptsize (r \; – \; r) =\left( \scriptsize 1 \; – \; \normalsize \frac{1}{4} \right)$$ Â

$$\normalsize \frac{3}{2} \scriptsize p = \normalsize \frac{3}{4}$$

Multiply both sides by 2

i.e.Â  Â  Â  Â  3p = $$\frac{3}{2}$$

Divide both sides by 3

i.e. Â  p = $$\frac{1}{2}$$

Substitute for p in equation (iii)

i.e. Â  Â  $$\frac{1}{2} \scriptsize + r = \normalsize \frac{1}{4}$$

i.e. Â  Â  r = $$\frac{1}{4} – \frac{1}{2}$$

i.e.Â  Â  r = $$– \frac{1}{4}$$

(b)    3p – 2r = 21       â€¦â€¦â€¦â€¦..i           (Multiply by 4)

4p + 5r = 5         â€¦â€¦â€¦â€¦..ii         (Multiply by 3)

i.e. Â  12p – 8r= 84 Â  Â  â€¦â€¦â€¦â€¦â€¦(iii)

12p + 15r = 15   â€¦â€¦â€¦â€¦â€¦(iv)

Subtract equation (iv) from (iii)

i.e.    -23r = 69

Divide both sides by -23

$$\frac {-23r}{23} = \frac {69}{23}$$

i.e.     r = -3

Substitute for r in equation (i)

i.e. Â  Â  3p – 2 (- 3 ) = 21

3p + 6 = 21

3p = 15

i.e.      p = 5

Check:

3p â€“ 2r = 21

3(5) â€“ 2(-3) = 21

15 + 6 = 21

21 = 21

error: